Decreasing Readmissions After Ileostomy Creation Through a Perioperative Quality Improvement Program. Issue 8 (5th July 2022) - Hsu, Angela Ting-Wei; Crawford, Todd C.; Zhou, Xun; Safar, Bashar; Efron, Jonathan; Atallah, Chady; Najjar, Peter A.; Girard, Andrea L.; Glover, Janelle C.; Warczynski, Tam; Cowell, Nicole A.; Cwik, Carol L.; et al.
Abstract : BACKGROUND: Readmission after ileostomy creation in patients undergoing colorectal surgery creates a significant burden on health care cost and patient quality of care, with a 30-day readmission rate of 40%. OBJECTIVE: This study aimed to evaluate the implementation of our perioperative quality improvement program, Decreasing Readmissions After Ileostomy Creation. DESIGN: Perioperative interventions were administered to patients who underwent ileostomy creation. SETTINGS: A single tertiary care academic center. PATIENTS: Eighty patients participated in this program from February 2020 to January 2021. MAIN OUTCOME MEASURES : The primary outcomes measured were 30-day readmission rates and causes of readmission, which were compared to a historical national database. Descriptive statistics were used to evaluate the effectiveness of this quality improvement program. RESULTS: Eighty patients were enrolled in this prospective quality improvement program. The mean age was 52 (±15.06) years. The most common indication for patients undergoing creation of an ileostomy was colorectal cancer (40%; n = 32). The overall 30-day readmission rate was 8.75% (n = 7) throughout the study period, which was significantly lower than historical cohort data (20.10%; p = 0.01). Among the 7 readmitted patients, 3 (3.75%) were readmitted due to dehydration. The most significant associated risk factor for all-cause readmission was urgent/emergent operative status, which was associated with an increased risk of readmission ( p = 0.01). The 3 readmitted patients with dehydration had a mean Dehydration Readmission After Ileostomy Prediction risk score of 11.71 points, compared to 9.59 points in nondehydrated patients, who did not require readmission ( p = 0.38). LIMITATIONS: This study is limited by its small sample size (N = 80). CONCLUSIONS: The Decreasing Readmissions After Ileostomy Creation program has been successful in reducing both the all-cause readmission rate and readmission due to dehydration both within an academic tertiary care referral center and in comparison with historical readmission rates. See Video Abstract at http://links.lww.com/DCR/B894 . DISMINUCIÓN DE LA READMISIÓN DESPUÉS DE LA CREACIÓN DE UNA ILEOSTOMÍA MEDIANTE UN PROGRAMA DE MEJORA DE LA CALIDAD PERIOPERATORIA: ANTECEDENTES: La readmisión después de la creación de una ileostomía en pacientes de cirugía colorrectal crea una carga significativa sobre el costo de la atención médica y la calidad de la atención del paciente, con una tasa de readmisión a los 30 días que llega al 40%. OBJETIVO: Este estudio tiene como objetivo evaluar la implementación de nuestro programa de mejora de la calidad perioperatoria que disminuyen los reingresos después de la creación de ileostomía. DISEÑO: Se administraron intervenciones perioperatorias a pacientes que se sometieron a la creación de una ileostomía. AJUSTE: Se trataba de un único centro académico de atención terciaria. PACIENTES: Participaron 80 pacientes en este programa desde febrero de 2020 hasta enero de 2021. PRINCIPALES MEDIDAS DE RESULTADO: Los principales resultados medidos fueron las tasas de reingreso a los 30 días y las causas de reingreso, que se compararon con una base de datos histórica nacional. Se utilizaron estadísticas descriptivas para evaluar la eficacia de este programa de mejora de la calidad. RESULTADOS: Ochenta pacientes se inscribieron en este programa prospectivo de mejora de la calidad. La edad media fue de 52 (± 15, 06) años. La indicación más común para los pacientes que se sometieron a la creación de una ileostomía fue el cáncer colorrectal (40%, n = 32). La tasa general de reingreso a los 30 días fue del 8, 75% (n = 7) durante todo el período de estudio, lo que fue significativamente más bajo que los datos históricos de la cohorte (20, 10%, p = 0, 01). Entre los 7 pacientes readmitidos, tres (3, 75%) fueron readmitidos por deshidratación. El factor de riesgo asociado más significativo para la readmisión por todas las causas fue el estado operatorio urgente / emergencia, que se asoció con un mayor riesgo de readmisión (p = 0, 01). Los tres pacientes readmitidos con deshidratación tuvieron una puntuación de riesgo promedio de readmisión por deshidratación después de la predicción de ileostomía de 11, 71 puntos, en comparación con los pacientes no deshidratados, que no requirieron readmisión (media, 9, 59 puntos, p = 0, 38). LIMITACIONES: Este estudio está limitado por su pequeño tamaño de muestra (n = 80). CONCLUSIONES: El programa de disminución de las readmisiones después de la creación de una ileostomía ha logrado reducir tanto la tasa de readmisión por todas las causas como la readmisión por deshidratación, tanto dentro de un centro académico de referencia de atención terciaria como en comparación con las tasas históricas de readmisión. Consulte Video Resumen en http://links.lww.com/DCR/B894 . (Traducción—Dr Yolanda Colorado )